Posterior fossa subdural haematoma associated with anticoagulant therapy. Issue 1 (February 1971) - Capistrant, T.; Goldberg, R.; Shibasaki, H.; Castle, D.
Abstract : This is a report of spontaneous posterioir fossa subdural haematoma associated with anticoagulation therapy. The possibility of posterior fossa lesions related to spontaneous haemorrhage is suggested by the combination of severe headache and increasing disturbance of consciousness associated with signs of brain-stem decompensation. A thorough neurological evaluation including appropriate contrast studies will help rule out a supratentorial lesion. This is a neurological emergency which can be successfully treated by early detection and prompt surgical decompression. This is the second reported case of spontaneous subdural haematoma of the posterior fossa occurring during anticoagulant therapy.